Antibacterial Activity of Hydroalcoholic Extract of Terminalia chebula Retz. on Different Gram-positive and Gram-negative Bacteria - Agrawal, Ashish (International Journal of Pharmaceutical & Biological Archive, 2011)
The present study describes the anti-bacterial activity of hydro-alcoholic extract of Terminalia chebula Retz fruit against microorganism like: Bacillus substils, Staphylococcus aureus, Staphylococcus epidermis, Escherichia coli, Staphylococcus flexineria and Pseudomonas aeruginosa. For this purpose hydro-alcoholic extract of fruit were prepared and tested by â€œDisc Diffusion Methodâ€. As a result of this study it was found that the extract of fruit generally revealed anti-bacterial activity against both gram-positive bacteria (B. subtils, S. aureous and S.epidermis) and gram-negative bacteria (E. coli, S. flexineria and S. auriginosa).